Research of Fuzzy Control Strategy of Coaxial Parallel Hybrid Electric Vehicle - Gao Longfei; Zhang Ruiliang; Chen Lianchun (Jixie chuandong)
In order to improve the fuel economy of coaxial parallel hybrid electric vehicle, the driver intention is used as the input variable of the fuzzy design to realize the fuzzy recognition of the driver intention, with considering the structural characteristics, working process and energy flow mode of coaxial parallel hybrid system. Fuzzy control torque distribution strategy based on recognition of driving intention is established in Matlab/Simulink, and joint simulation is performed with Cruise under NEDC cycle condition. The results show that, under the premise of satisfying the dynamic performance, compared with the logic threshold based on torque distribution control strategy, the proposed control strategy can effectively improve the working point of the engine, and can reduce the comprehensive fuel consumption of 100 kilometers about 3.2%, which satisfies the vehicle dynamics, and further improves the fuel economy.